Sibling action : the genealogical structure of modernity - Engelstein, Stefani, 1970- (Columbia University Press, 2017)
Beginning in the late eighteenth century, Europeans embarked on a new way of classifying the world, devising genealogies that determined degrees of relatedness by tracing heritage through common ancestry. This methodology organized historical systems into family trees, transforming the closest contemporaneous terms on trees of languages, religions, races, nations, species, or individuals into siblings. Encompassing political fraternity, sister languages, racial discourse on brotherhood, evolutionary sibling species, and intense, often incestuously inclined brother-sister bonds in literature, siblinghood stands out as a ubiquitous-yet unacknowledged-conceptual touchstone across the European long nineteenth century. In all such systems the sibling term, not-quite-same and not-quite-other, serves as an active fault line, necessary for and yet continuously destabilizing definition and classification. In her provocative book, Stefani Engelstein explores the pervasive significance of sibling structures and their essential role in the modern organization of knowledge and identity. Sibling Action argues that this relational paradigm came to structure the modern subject, life sciences, human sciences, and collective identities such as race, religion, and gender.